Pemberdayaan Potensi Guru SMK Kota Tegal dalam Pembuatan Hand Sanitizer untuk Pandemi Covid-19 - Heru Nurcahyo (Universitas Lancang Kuning, 2021)
Increasing the strengthening of teacher competency through Community Service activities in the preparation of hand sanitizers in deciding the spread of the Covid-19 outbreak for teachers and laboratory assistants of Harapan Bersama Tegal City. The limitations of the teachers and laboratory assistants in making hand sanitizers quickly and productively became the main study material discussed. The solution offered is to provide mentoring and training to teachers and laboratory assistants for the manufacture of hand sanitizers such as liquid forms, gels and herbal extracts. The training aims to improve the competence of teachers and laboratory assistants in increasing understanding in making hand sanitizer dosage forms to take a role in deciding the spread of covid outbreaks. This training activity is carried out for 3 days with material, making sedans and evaluating preparations to produce good hand sanitizers. The results of this PKM (Community service) found an increase in science and competence in the manufacture of hand sanitizer formulations by 21%.